Determinants of Capital Structure in Non-Financial Companies - Chairul Akmal (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
The purpose of this study is to determine whether company profitability, company size, growth rate and company asset structure affect the capital structure decisions of non-financial public companies included in the Kompas 100 index. The research method uses quantitative methods with descriptive statistical approaches and inferential statistics through regression analysis techniques. panel data. The results show that the effect of profitability, firm size, growth, and firm asset structure together on the capital structure of non-financial public companies listed in the Kompas 100 Index is positive and significant